Adsorption and superficial transport of oil on biological and bionic superhydrophobic surfaces: a novel technique for oil–water separation. (20th March 2020) - Barthlott, W.; Moosmann, M.; Noll, I.; Akdere, M.; Wagner, J.; Roling, N.; Koepchen-Thomä, L.; Azad, M. A. K.; Klopp, K.; Gries, T.; Mail, M.
Abstract : Superhydrophobicity is a physical feature of surfaces occurring in many organisms and has been applied (e.g. lotus effect) in bionic technical applications. Some aquatic species are able to maintain persistent air layers under water ( Salvinia effect) and thus become increasingly interesting for drag reduction and other 'bioinspired' applications. However, another feature of superhydrophobic surfaces, i.e. the adsorption (not absorption) and subsequent superficial transportation and desorption capability for oil, has been neglected. Intense research is currently being carried out on oil-absorbing bulk materials like sponges, focusing on oleophilic surfaces and meshes to build membranes for oil–water separation. This requires an active pumping of oil–water mixtures onto or through the surface. Here, we present a novel passive, self-driven technology to remove oil from water surfaces. The oil is adsorbed onto a superhydrophobic material (e.g. textiles) and transported on its surface. Vertical and horizontal transportation is possible above or below the oil-contaminated water surface. The transfer in a bioinspired novel bionic oil adsorber is described. The oil is transported into a container and thus removed from the surface. Prototypes have proven to be an efficient and environmentally friendly technology to clean oil spills from water without chemicals or external energy supply. This article is part of the theme issue 'Bioinspired materials and surfaces for green science and technology (part 3)'.